Evidence that Temminck described Felis aurata in 1825, not 1827. Issue 1 (April 2022) - Kitchener, Andrew C.; Simo, Franklin T.; Mugerwa, Badru; Sanderson, James G.
Abstract : The African golden cat, Caracal aurata, ranges from west through central to east Africa and is categorized as Vulnerable on the IUCN Red List of Threatened Species. Coenraad J. Temminck (1778–1858) described Felis aurata (African golden cat) and other new felid species in the fourth of seven monographs collected in the first volume of his Monographies de mammalogie, which was dated 1827 on the title-page. For nearly two centuries, Temminck's description of Felis aurata has therefore been cited as published in 1827. However, this is in error because the different monographs were published as they were completed and later compiled into volumes. The actual date of issue for the fourth monograph was 1825, so that the correct current citation for the African golden cat should be Caracal aurata (Temminck, 1825). This revised citation date is also applicable to the Iberian lynx, Lynx pardinus (Temminck, 1825), which is categorized as Endangered on the IUCN Red List.